Connecting with older people: multiple transitions in same place - Marshall, Fiona (Springer International Publishing, 2017)
This chapter presents an overview about sustaining dignified care for stroke patients nearing the end of their hospital stay. It explores the conceptualisation of empathy in practice in relation to a recovery trajectory of multiple transitions. Broadly these transitions concretise a cumulative change process as preparation for discharge is initiated. Approaching the discharge transition can be difficult for all concerned as organisational demands converge as a cluster of divergent mixed emotions, expectations and experiences among staff and patients. Minimal attention has been given to the emotional impact of multiple transitions characteristic of lengthy stays and so this chapter draws on the outcomes of an ethnographic study which sought to understand the process more thoroughly through the experiences of patients and staff.